Policy Action for Climate Change Adaptation. Project synthesis report, 2014-2020 - Acosta, Mariola; Bamanyaki, Patricia A.; Solomon, Dawit; Alemayehu, Sintayehu; Girvetz, Evan Hartunian; Tesfaye, Lidya; Muchunguzi, Perez (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Climate change is increasingly threatening the livelihoods of millions of smallholder farmers in Sub-Saharan Africa. Increased climate variability, including changes in mean temperatures, variation in the onset of rains, and increases in extreme weather events, are directly affecting the growing seasons of commercial and subsistence crops, significantly disturbing socio-economic activities in the agricultural sector and leaving many smallholder farmers in a situation of food insecurity and malnutrition. Within this context, it has become increasingly crucial that governments and relevant stakeholders in the region develop policy strategies that help adapt to changes in climate and help build more resilient food systems. To support these policy processes, the CGIAR Program of Climate Change, Agriculture, and Food Security (CCAFS) started in 2014 the seven-year initiative “Policy Action for Climate Change Adaptation (PACCA)”. PACCA consisted of a first phase (2014-2017), which operated under the project entitled “Influencing and linking national and local level policies and institutions to adopt climate-resilient food systems” in Uganda and Tanzania, and a second phase (2018-2020), which operated under the project entitled “Stimulating adoption of nutrition sensitive climate smart agriculture by aligning national level agenda with implementation” in Uganda and Ethiopia. This report summarizes the main findings that emerged from Phase 1 and 2 of PACCA, presents the lessons learnt and achievements for climate change policy action work and reflects on both projects impact pathways, providing some recommendations for future policy initiatives in the region.